Background and fingerprint characteristics of anthropogenic 236U and137Cs in soil and road dust samples collected from Beijing and Zhangjiakou, China. (January 2021) - Shao, Yang; Yang, Guosheng; Luo, Min; Xu, Diandou; Tazoe, Hirofumi; Yamada, Masatoshi; Ma, Lingling
Abstract: 236 U has attracted more attention as an environmental tracer in recent years. However, in-depth study of 236 U in terrestrial environments is still rare in China. Data on 236 U and 137 Cs concentrations in soil and road dust samples collected from Beijing and Zhangjiakou, China were obtained to demonstrate the background and distinct characteristics of anthropogenic 236 U and 137 Cs. 236 U and 137 Cs were detected in the range of (1.10–7.90) × 10 7 atoms g −1 and below the method limits of detection to 5.30 Bq kg −1 . A clear characteristic was observed in road dust, where 236 U concentrations increased with decreasing of sample particle size. Soil samples showed an irregular characteristic, but the highest 236 U concentrations were observed in particle size fraction of <0.053 mm in both samples. This phenomenon was caused by U chemical properties, higher specific surface areas and organic compounds in fine particles. Anthropogenic radionuclides fingerprint characteristics in <0.053 mm samples were specially discussed. 236 U/ 238 U atom ratios were detected in the range of (0.627–3.38) × 10 −8 . A weak correlation between anthropogenic 236 U and natural U isotopes were observed. The intermediate correlation between 236 U and 137 Cs indicated somewhat distinct migration behavior of these two radionuclides in soil after release to the environment. The released amount of 236 U from global fallout during the period of atmospheric nuclear weapons testing was roughly estimated to be 1300 ± 448 kg. These results could be used as fingerprint information for anthropogenic 236 U migration behavior and tracer application in environment. Graphical abstract: Image 1 Highlights: Measured 236 U were (2.13–7.52) × 10 7 atoms g −1 in Chinese soil samples. Measured 236 U were (1.10–7.90) × 10 7 atoms g −1 in Chinese road dust samples. Fine soil particles of <0.053 mm size fraction had the highest 236 U concentrations. Estimated release of 236 U was 1300 ± 448 kg due to nuclear weapons testing.